The prevalence of urinary incontinence in men and women aged 40 years or over in China, Taiwan and South Korea: A cross‐sectional, prevalence‐based study. Issue 3 (23rd March 2020) - Sumarsono, Budiwan; Jong, Jar Jar; Wang, Jian‐Ye; Liao, Limin; Lee, Kyu‐Sung; Yoo, Tag Keun; Liu, Shih‐Ping; Chuang, Yao‐Chi
Abstract: Objectives: To assess prevalence of urinary incontinence (UI), including urgency UI (UUI), stress UI (SUI) and mixed UI (MUI) in individuals aged ≥40 years in China, Taiwan and South Korea. Method: This was a post hoc analysis of a cross‐sectional, questionnaire‐based internet survey. Participants were asked questions relating to urinary symptoms, health‐related quality of life (HRQoL) and mental health (using the HRQoL 12‐item short form health survey mental health and physical domains, and the Hospital Anxiety and Depression Scale), visits to healthcare professionals (HCPs) for any reason or for urinary symptoms, treatments for urinary symptoms and treatment satisfaction. Results: Of 8284 survey participants, 1818 (22%) reported any UI (men 17.3%, women 26.4%). MUI was the most prevalent (overall 9.7%, men 6.8%, women 12.6%) followed by SUI (overall 7.9%, men 5.1%, women 10.7%) and UUI (overall 4.3%, men 5.5%, women 3.2%). HRQoL, anxiety and depression scores were poor in all participants with UI; MUI was associated with the worst scores. Of the participants with UI, 46.9% visited HCPs for urinary symptoms (highest proportion [62.7%] among participants with MUI). Approximately 80% of participants with UI followed treatment, with prescribed medicine being the most common form (38.1%). Over half of participants (59.6%) were somewhat, very, or extremely satisfied with their treatment. MUI was associated with least satisfaction. Conclusion: UI was associated with substantial problems, including an adverse impact on HRQoL. Medication failed to satisfy many individuals with UI. Efforts to educate the public and physicians about the impact of UI could improve diagnosis and treatment rates.